Research on Intelligent Automation Control Strategies for Reducing Building Energy Consumption and Carbon Emissions - Chen, Rongdong (European Journal of AI, Computing & Informatics, 2026)
This research investigates intelligent automation control strategies aimed at reducing building energy consumption and carbon emissions. By integrating advanced control algorithms, sensor technologies, and data-driven optimization techniques, the study explores innovative solutions to enhance energy efficiency in buildings. A comprehensive methodology is employed, encompassing system modeling, experimental validation, and performance analysis. Results demonstrate significant potential for intelligent automation to minimize energy usage and emissions while maintaining occupant comfort. The findings provide actionable insights for sustainable building management and contribute to global efforts in mitigating climate change.